Tocilizumab Use in a Chronic Hemodialysis Patient for the Management of COVID-19-Associated Pneumonia and Acute Respiratory Distress Syndrome. (23rd November 2020) - Gupta, Sudeendra; Madhyastha, Rakesh; Hamed, Fadi; Balkis, Maher; El Nekidy, Wasim; Attallah, Nizar
Abstract : Novel coronavirus disease 2019 (COVID-19) is a highly infectious, rapidly spreading viral disease. As of writing this article, there are over 4.4 million people affected by COVID-19, and unfortunately, 300, 000 have succumbed to the infection. In this article, we address a particularly more susceptible group of the population of end-stage renal disease (ESRD) patients on dialysis who may potentially benefit from being treated with tocilizumab. The use of tocilizumab has not been reported widely in ESRD patients on dialysis to treat COVID-19. In this case report, we describe a patient with ESRD on hemodialysis who was admitted to the intensive care unit, with severe pneumonia secondary to COVID-19 infection. This patient was treated with tocilizumab 400 mg intravenous and had a favorable outcome with no apparent adverse events.